Tanggung Gugat Direksi Terhadap Kelalaian Penerapan Good Corporate Governance dalam PT yang Mengakibatkan Kepailitan - Kurniawan, Rio Indra; Nurfuadi, Muhammad Aliffian; Fikry, Aiman; Fitriani, Alya (Dinasti Research, 2026)
The Board of Directors is an organ in a limited liability company that has full authority and responsibility for managing the company for the benefit of the company both inside and outside the court. The Board of Directors in carrying out these duties and authorities must comply with the principles of Good Corporate Governance (GCG) so that the company can run well. In this case, there is a problem if the board of directors is negligent or fails to apply the principles of GCG so that a company experiences losses that can result in the company becoming bankrupt. The problem being studied is an explanation of the principles of GCG in a limited liability company and whether the board of directors is responsible for negligence in implementing the principles of GCG that results in bankruptcy. This research uses a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The results of this research are in the form of an explanation of the GCG principles in the form of transparency, accountability, responsibility, independence, equality, and fairness, directors are responsible if they fail to apply the GCG principles in accordance with Article 104 paragraph (2) of Law No. 40 of 2007 concerning Limited Liability Companies.